Samal kulintang music - Eugenio, Ardel Biri
This writer aims to assist the reader in the overview, appreciation and understanding of Philippine indigenous music in general and kulintang music in particular. It is also the aim of the paper to present a transcription of kulintang pieces with analysis.
Thesis (B.M.)--University of the Philippines, Diliman.
Keywords: Samals (Philippine people)xMusic.; Kulintang music -- Samals (Philippine people).